The biogeochemistry of bioactive trace elements cadmium and cobalt in the Southern Ocean, Atlantic Sector - Loock, Jean Christian (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.